Comparison of level of endothelial progenitor cells (epcs) in astrocytoma to adjacent normal brain tissue - Chee How, Ch’ng (2014)
Introduction: Astrocytomas are the most common primary brain tumors which account for up to two third of all tumors of glial origin and especially the high grade astrocytoma are known to be highly vascularized. Previous studies suggest that vascularization of astrocytoma especially high grade astrocytoma, is contributed by several mode of vascularization which explained, the resistance of the tumor to anti-angiogenic therapy. Endothelial progenitor cells are believed to play an important role in vascularization of astrocytoma, directly by vasculogenesis or indirectly by secreting various proangiogenic factors and possible next target of therapy. Objective: To compare the EPCs level in between the astrocytoma tissue samples to the adjacent normal brain tissue and subanalysed, by comparing the EPCs level in high grade astrocytoma to low grade astrocytoma. Methods: A total of 17 patients with astrocytoma, 11 patients with high grade astrocytoma (WHO Grade III and IV) and 6 patients with low grade astrocytoma (WHO Grade I and II), were recruited from Hospital Universiti Sains Malaysia. All patients underwent surgery for astrocytoma, tumor and normal adjacent brain tissues were collected. Tumor and normal adjacent brain tissues were sliced and stained with CD 133 and VEGFR-2 marker and followed by immunohistochemical analysis to determine the EPCs in the tumor and normal adjacent brain tissue. Results: The levels of EPCs were significantly higher in the astrocytoma compared to adjacent normal brain tissue. Sub analysis of the study, compared the level of EPCs in the high grade astrocytoma to the low grade astrocytoma, do not showed significant difference. Conclusions: This study showed higher level of EPCs in the astrocytoma as compared to the normal adjacent brain tissue suggest the possibility of EPCs play a role in astrocytoma vascularizatio